A vertical parabola with vertex (1,-4) and focus (1,-2) is given. It is required to find the standard form of the equation for the parabola.
Recall that the equation of a Vertical Parabola with vertex (h,k) and focus (h,k+1/4a) is given as:
![y=a(x-h)^2+k](https://img.qammunity.org/2023/formulas/mathematics/college/97p0xsjs0cwme4ddvwkim2cbbqprhnlhsv.png)
Compare the given vertex (1,-4) with the form (h,k). It follows that:
![h=1,k=-4](https://img.qammunity.org/2023/formulas/mathematics/college/kc9in6bd1nwd0gu4qno5tsx7y17gabc7wn.png)
Compare the given focus (1,-2) with the form (h,k+1/4a). It follows that:
![k+(1)/(4a)=-2](https://img.qammunity.org/2023/formulas/mathematics/college/s3edbl51kx4iztyb8ay0efsl1tnxynsd5z.png)
Substitute k=-4 into the equation and find the value of a:
![\begin{gathered} -4+(1)/(4a)=-2 \\ \Rightarrow(1)/(4a)=-2+4 \\ \Rightarrow(1)/(4a)=2 \\ \Rightarrow4a=(1)/(2) \\ \Rightarrow a=(1)/(8) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/hztbbhjx3b7zndfduezfnfa0180hm3g07w.png)
Substitute k=-4, h=1, and a=1/8 into the equation of a vertical parabola:
![y=(1)/(8)(x-1)^2+(-4)](https://img.qammunity.org/2023/formulas/mathematics/college/w5vgcx0ecwzf3vdm9ofvsmyv0pt1hfjk2x.png)
Rewrite the equation in standard form as follows:
![\begin{gathered} y+4=(1)/(8)(x-1)^2 \\ \Rightarrow8(y+4)=(x-1)^2 \\ \text{ Swap the sides of the equation:} \\ \Rightarrow(x-1)^2=8(y+4) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/rmjj786r0xcvduy1mdbuelq627illtwzkr.png)
Recall that the Directrix of a vertical parabola is represented by the equation:
![y=k-(1)/(4a)](https://img.qammunity.org/2023/formulas/mathematics/college/flo0u61bii99mjywqa8w8qiib475r6vfiz.png)
Substitute k=-4 and a=1/8 into the equation of directrix:
![\begin{gathered} y=-4-(1)/(4((1)/(8)))=-4-(1)/((1)/(2))=-4-2=-6 \\ \Rightarrow y=-6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/bm4ah4imc19wkhuwor8apn4d9tphkh5oiw.png)
Hence, the correct answer is (x-1)²=8(y+4); y=-6.
The correct answer is (x-1)² = 8(y+4) ; y = - 6. (second option)